EVALUATION OF THE APPLICABILITY OF A CHILD-APPROPRIATE HIGH THROUGHPUT HPLC-MS/MS METHOD FOR THE DETERMINATION OF ENALAPRIL AND ENALAPRILAT IN SMALL SAMPLE VOLUMES OF SERUM AND URINE WITHIN A GCLP-COMPLIANT ENVIRONMENT. Issue 1 (14th December 2015) - Schäfer, Julia; Burckhardt, Björn B.; Tins, Jutta; Läer, Stephanie
Abstract : Background: Heart failure is a life-threatening disease in neonates up to adolescents. The angiotensin-converting enzyme inhibitor enalapril is a recommended therapy in paediatric heart failure, although it is not labelled for patients Objective: Proof of concept of the paediatric tailored assays by verification of the reliable conduct of sample analysis according to international bioanalytical guidelines and determination of enalapril and its active metabolite enalaprilat in the LENA phase I study. Methods: All LENA phase I samples were analysed applying the developed high throughput analysis for enalapril and enalaprilat via HPLC-MS/MS. According to the established LENA GCLP-compliant quality system, the evaluation of all study samples was conducted by using freshly prepared quality standards to obtain calibration curves of enalapril and enalaprilat in serum and urine. Results: In total, 22 calibration curves in serum and 7 in urine were required to investigate all samples of the phase I study of LENA. All 29 calibration curves complied with the limits of FDA and EMA bioanalytical guidelines and the applicability of the established high throughput method in the GCLP environment was proven. About 2100 study samples were successfully determined within 26 days. Conclusion: The developed paediatric tailored high throughput HPLC-MS/MS analysis proved its applicability in a GCLP-compliant environment and is suitable for the upcoming phase II and phase III studies of the LENA project focussing on paediatric patients. The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA).